Multimodality assessment of left ventricular dysfunction in Takayasu arteritis and familial hypercholesterolaemia. (31st July 2017) - Okada, Atsushi; Takahama, Hiroyuki; Ogura, Masatsune; Morita, Yoshiaki; Konma, Junichi; Yoshida, Shuzo; Makino, Shigeki; Takashio, Seiji; Amaki, Makoto; Ohara, Takahiro; Hasegawa, Takuya; Sugano, Yasuo; et al.
Abstract: Although left ventricular (LV) systolic dysfunction in patients suffering from Takayasu arteritis (TA) has been reported, little is known regarding the development of heart failure in these patients. We report a novel finding of active TA and familial hypercholesterolaemia presenting with severe LV dysfunction through multimodality assessments of LV systolic dysfunction.